INKUISISI GEREJA KATOLIK TERHADAP UMAT ISLAMDI SPANYOL - Nur Fitriyana, Nur Fitriyana (JIA (Jurnal Ilmu Agama), 2016)
For Catholics, Jesus was the only legitimate way to salvation. Then the consequence of that was the creed outside the church as heretical teaching. The Inquisition was a tribunal set up by the church to investigate (inquirere from Latin), whether the statement of faith of the members in accordance  with  the  teachings  of  the  church.  Based  on  historical  fact,  there  are  three  kinds  of Inquisition in church history, namely: 1) the Inquisition held in 1184 in southern France, to handle Catharists. 2) The Roman Inquisition that began in 1542 and 3) Spanish Inquisition that began in 1478, organized by the Spanish government to investigate the conversos ,Catholics who had been the  Jewish  and  Muslim,  or  those  who  pretend  to  be  Catholic.  There  are  seventeen  courts  of  the Inquisition  in  Spain  and  10  heretics  were  burned.  In  the  1479  because  of  pressure  from  the authorities of the Catholic Church in Spain, Ferdinand II of Aragon and Isabella I of Castile, Pope Sixtus IV formed an independent Spanish Inquisition, led by the high council and implementing the Great Inquisition.